2018
DOI: 10.5194/acp-18-13115-2018
|View full text |Cite
|
Sign up to set email alerts
|

Simulated and observed horizontal inhomogeneities of optical thickness of Arctic stratus

Abstract: Abstract. Two-dimensional horizontal fields of cloud optical thickness τ derived from airborne measurements of solar spectral, cloud-reflected radiance are compared with semi-idealized large eddy simulations (LESs) of Arctic stratus performed with the Consortium for Small-scale Modeling (COSMO) atmospheric model. The measurements were collected during the Vertical Distribution of Ice in Arctic Clouds (VERDI) campaign carried out in Inuvik, Canada, in April/May 2012. The input for the LESs is obtained from coll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
(81 reference statements)
1
6
0
Order By: Relevance
“…For Ci-Cs the opposite applies: the absolute U c in COT DSR retrieval is 0.1 for all cases, independent of the COT input value. Similar behaviours of the uncertainties of COT DSR estimations are also presented in Serrano et al (2014).…”
Section: Sensitivity Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…For Ci-Cs the opposite applies: the absolute U c in COT DSR retrieval is 0.1 for all cases, independent of the COT input value. Similar behaviours of the uncertainties of COT DSR estimations are also presented in Serrano et al (2014).…”
Section: Sensitivity Analysissupporting
confidence: 78%
“…A number of studies have presented methods for the retrieval of COT using data from ground-based instruments, for example, from lidars (Gouveia et al, 2017), broadband pyranometers (Leontyeva and Stamnes, 1994; Barnard and Long, 2004;Qiu, 2006), sunphotometers (Min and Harrison, 1996;Chiu et al, 2010) or UV radiometers (Serrano et al, 2014). With ground-based microwave instruments the liquid water path (LWP) is determined (Dupont et al, 2018), which can be used to calculate the cloud optical thickness, knowing or assuming r eff (Stephens, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Cloud resolving models (1 km horizontal and 30 m vertical resolution; Luo et al, 2008) and large eddy simulations (LESs, below 100 m horizontal and 15 m vertical resolution; Loewe et al, 2017) resolve small-scale cloud processes and are used to improve the subgrid mixed-phase cloud parameterization of GCMs. In order to evaluate the performance of these highresolution simulations, adequately resolved observations are needed (Werner et al, 2014;Roesler et al, 2017;Schäfer et al, 2018;Egerer et al, 2019;Neggers et al, 2019;Schemann and Ebell, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a comparison of large eddy simulations to aircraft observations for well-defined situations can give valuable insights into physical processes within the Arctic atmosphere. Such simulations can be particularly useful when the high resolution of a large eddy set-up is explicitly needed to allow for a comparison with small scale phenomena like in-cloud turbulence (Mech et al, 2020) or cloud-top inhomogeneity (Schäfer et al, 2018;Ruiz-Donoso et al, 2020) that are observed from the airborne remote sensing. To avoid the need for large computational resources but still be able to resolve many processes that act on scales that cannot be captured by GCMs, limited area simulations with grid sizes on the order of a few kilometers where (deep) convection does not need to be explicitly parameterized can offer a good compromise.…”
Section: Introductionmentioning
confidence: 99%